ESCMID Study Group for Infections in Compromised Hosts (ESGICH) Consensus Document on the safety of targeted and biological therapies: an infectious diseases perspective (Immune checkpoint inhibitors, cell adhesion inhibitors, sphingosine-1-phosphate receptor modulators and proteasome inhibitors). (June 2018) - Redelman-Sidi, G.; Michielin, O.; Cervera, C.; Ribi, C.; Aguado, J.M.; Fernández-Ruiz, M.; Manuel, O.
Abstract: Background: The present review is part of the European Society of Clinical Microbiology and Infectious Diseases (ESCMID) Study Group for Infections in Compromised Hosts (ESGICH) consensus document on the safety of targeted and biological therapies. Aims: To review, from an infectious diseases perspective, the safety profile of immune checkpoint inhibitors, LFA-3–targeted agents, cell adhesion inhibitors, sphingosine-1-phosphate receptor modulators and proteasome inhibitors, and to suggest preventive recommendations. Sources: Computer-based Medline searches with MeSH terms pertaining to each agent or therapeutic family. Content: T-lymphocyte–associated antigen 4 (CTLA-4) and programmed death (PD)-1/PD-1 ligand 1 (PD-L1)-targeted agents do not appear to intrinsically increase the risk of infection but can induce immune-related adverse effects requiring additional immunosuppression. Although CD4 + T-cell lymphopenia is associated with alefacept, no opportunistic infections have been observed. Progressive multifocal leukoencephalopathy (PML) may occur during therapy with natalizumab (anti–α4-integrin monoclonal antibody (mAb)) and efalizumab (anti-CD11a mAb), but no cases have been reported to date with vedolizumab (anti-α4β7 mAb). In patients at high risk for PML (positive anti-JC polyomavirus serology with serum antibody index >1.5 and duration of therapy ≥48 months), the benefit–risk ratio of continuing natalizumab should be carefully considered. Fingolimod induces profound peripheral blood lymphopenia and increases the risk of varicella zoster virus (VZV) infection. Prophylaxis with (val)acyclovir and VZV vaccination should be considered. Proteasome inhibitors also increase the risk of VZV infection, and antiviral prophylaxis with (val)acyclovir is recommended. Anti- Pneumocystis prophylaxis may be considered in myeloma multiple patients with additional risk factors (i.e. high-dose corticosteroids). Implications: Clinicians should be aware of the risk of immune-related adverse effects and PML in patients receiving immune checkpoint and cell adhesion inhibitors respectively.